1993
DOI: 10.1002/pola.1993.080311229
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of micron‐size monodisperse polymer particles by dispersion copolymerization of styrene with poly(2‐oxazoline) macromonomer

Abstract: This article describes the preparation of micron‐size monodisperse polymer particles by dispersion copolymerization of styrene with a poly(2‐oxazoline) macromonomer in an aqueous ethanol solution. The macromonomer acted as a comonomer as well as a stabilizer. The diameter of the particles increased as the concentration of the macromonomer decreased. The higher the molecular weight of the macromonomer, the smaller the particle size. The copolymerization in the solvent containing higher water content gave smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…The interest in such reactive molecules have been recently demonstrated by the group of Kobayashi [1,2]. These authors have shown that the same size of polystyrene particles (about 2 m) can be obtained upon replacing high polymers of poly(alkyl oxazoline) by macromonomers of much lower molecular weight of the same structure with a styrenic end group.…”
Section: Introductionmentioning
confidence: 96%
“…The interest in such reactive molecules have been recently demonstrated by the group of Kobayashi [1,2]. These authors have shown that the same size of polystyrene particles (about 2 m) can be obtained upon replacing high polymers of poly(alkyl oxazoline) by macromonomers of much lower molecular weight of the same structure with a styrenic end group.…”
Section: Introductionmentioning
confidence: 96%
“…9 -15 Kobayashi et al have reported the synthesis of polystyrene particles by dispersion copolymerization of poly(2-oxazoline) macromonomers with styrene. 11 They also prepared poly(vinyl acetate) particles using poly(2-oxazoline) macromonomers as a steric stabilizer in water. 12 Winnik et al have studied the dispersion copolymerization of styrene or n-butyl methacrylate with p-alkylstyrene terminated poly(ethylene glycol) (PEG) macromonomers in methanol/water mixed solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In emulsion polymerization, the emulsifier stabilizes the water-insoluble monomer particles. Recently, preparations of monodisperse polymer particles by using a hydrophilic macromonomer have been reported, such as poly(N -vinylpyrrolidone) (2,3), poly(2-alkyl-2-oxazoline) (4,5), poly(ethylene oxide) (PEO) (3,(6)(7)(8), poly(methacrylic acid) (PMA) (9,10), and poly(acrylic acid) 1 To whom correspondence should be addressed. (11,12), instead of using a homopolymer as a stabilizer.…”
Section: Introductionmentioning
confidence: 99%